2011
DOI: 10.1186/1756-0500-4-44
|View full text |Cite
|
Sign up to set email alerts
|

Novel sul I binary vectors enable an inexpensive foliar selection method in Arabidopsis

Abstract: BackgroundSulfonamide resistance is conferred by the sulI gene found on many Enterobacteriaceae R plasmids and Tn21 type transposons. The sulI gene encodes a sulfonamide insensitive dihydropteroate synthase enzyme required for folate biosynthesis. Transformation of tobacco, potato or Arabidopsis using sulI as a selectable marker generates sulfadiazine-resistant plants. Typically sulI-based selection of transgenic plants is performed on tissue culture media under sterile conditions.FindingsA set of novel binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Therefore, in all transformation vectors, the sul coding sequence was fused to the transit peptide from the Rubisco small subunit of pea ( Pisum sativum ) to target the Sul protein (i.e., the sulfonamide‐resistant DHPS) to the chloroplast. The successful generation of transgenic plants with these constructs in a number of plant species (Guerineau et al ., ; Wallis et al ., ; Hadi et al ., ; Thomson et al ., ) seemed to confirm the chloroplast localization of DHPS and the entire folate pathway. However, subsequently obtained evidence for a mitochondrial localization of DHPS and the downstream enzymes of the pathway has cast considerable doubt on the chloroplast location of the folate pathway in plants (Rébeillé et al ., ; Hanson and Gregory, , ).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, in all transformation vectors, the sul coding sequence was fused to the transit peptide from the Rubisco small subunit of pea ( Pisum sativum ) to target the Sul protein (i.e., the sulfonamide‐resistant DHPS) to the chloroplast. The successful generation of transgenic plants with these constructs in a number of plant species (Guerineau et al ., ; Wallis et al ., ; Hadi et al ., ; Thomson et al ., ) seemed to confirm the chloroplast localization of DHPS and the entire folate pathway. However, subsequently obtained evidence for a mitochondrial localization of DHPS and the downstream enzymes of the pathway has cast considerable doubt on the chloroplast location of the folate pathway in plants (Rébeillé et al ., ; Hanson and Gregory, , ).…”
Section: Introductionmentioning
confidence: 67%
“…For initial transformation experiments, vector p35S sul was used. It contains the sul cassette (driven by the CaMV 35S promoter and the RbcS transit peptide) that was used in all previous transformation studies that employed sulfadiazine selection (Guerineau et al ., ; Wallis et al ., ; Hadi et al ., ; Thomson et al ., ; Dal Bosco et al ., ). These experiments confirmed that transgenic plants can be obtained by selection for 20 or 25 mg/L sulfadiazine.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Approximately 100,000 T1 seeds from each of the three transformations were sown on flats of soil for approximately 10 d, then heavily misted with a solution of 500 mg L 21 sulfadiazine containing 0.03% (w/v) of the surfactant Silwet L-77, as described by Thomson et al (2011). Plants that survived the sulfadiazine application and displayed red fluorescence were transferred to pots of untreated soil and grown to maturity.…”
Section: Mutant Complementationmentioning
confidence: 99%
“…A fragment including 35S promoter, gene, and terminator was then extracted from these plasmids using SacI and ApaI and introduced into the multicloning site of pSUN (Thomson et al, 2011). After floral dipping, seedlings were selected using sulfadiazine.…”
Section: Plant Transformationmentioning
confidence: 99%